PkM: Workshop Implementasi Kurikulum Merdeka Belajar Bagi Guru IPS SMP di Kota Kediri - M. Anas; Mochamad Muchson; Sugiono Sugiono; Rr. Forijati; Subagyo Subagyo; Tri Yuliani (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to provide adequate understanding and skills for Social Science (IPS) teachers in junior high schools (SMP) in the city of Kediri related to the implementation of the Merdeka Belajar Curriculum (CMB) and the output of this activity is in the form of Differentiated Teaching Modules for IPS subjects in SMP. The community service method is in the form of a workshop including test activities (pre-test and post-test, CMB literacy tutorials and assignments (performance). The data analysis technique uses a paired sample test with the help of the SPSS V.23 application. The community service results show that 1) this service activity is effective because it has been able to improve the pedagogical competence of IPS teachers of SMP in the City of Kediri, 2) there are significant differences in the pedagogical competence of IPS teachers of SMP in the City of Kediri between before and after participating in the community service activities of CMB implementation workshops, and 3) resulted differentiated teaching modules of IPS subjects in SMP.